(untitled) (International Journal of Atharva, 2025)
Background: The hospitality industry is fundamentally reliant on its human capital, where the competencies and qualifications of both staff and management are critical determinants of service quality, guest satisfaction, and organizational success. These competencies encompass a blend of knowledge, skills, attitudes, and behaviors, which have been further reshaped by globalization, digital transformation, and the heightened expectations post-COVID-19. Formal education and vocational certifications are essential for aligning employee capabilities with rigorous industry standards. Objective: This study aimed to assess the competencies and qualifications of staff and management within the hospitality sector, focusing on demographic profiles, professional development experiences, and key behavioral competencies. Methods: A quantitative, cross-sectional survey was conducted among 200 employees and managers from selected five-star hotels in the Kathmandu Valley. Data were collected via a structured questionnaire using both online and paper-based formats. Analysis was performed using descriptive statistics to generate frequencies and percentages. Findings: The findings revealed a predominantly young workforce (70% aged 21-29) with a balanced gender distribution. A majority held a Bachelor’s degree (58%) and had previous hospitality experience (84.5%). Most respondents found their roles beneficial for professional growth (80%) and felt recognized for their contributions (64.5%). The primary reason for considering quitting was interpersonal issues with colleagues (28.5%), not low salary. High levels of self-reported competency were observed across key areas: ethical conduct (65.5% agree/strongly agree), time management (80.5%), customer-centric decision making (85%), and effective communication skills such as listening (90%) and encouraging others (88.5%). Conclusion: The study concludes that the workforce in five-star hotels in Kathmandu is well-educated, experienced, and possesses strong self-reported competencies crucial for hospitality roles. However, the young age profile suggests potential challenges with retention and career longevity. Job satisfaction appears to be influenced more by workplace relationships and role satisfaction than by financial compensation. Implication: The implications for hotel management are twofold. Firstly, there is a need to develop strategies that enhance team cohesion and interpersonal relationships to reduce attrition. Secondly, investing in continuous training and clear career progression pathways is essential to retain young talent and ensure the longevity of careers within the industry.